A Topical Combination of 0.1 % Rapamycin And 0.1 % Tacrolimus Ointment for the Treatment of Facial Angiofibromas in Tuberous Sclerosis Complex – A Pilot Study of 5 Cases - Jagati, Ashish; Buch, Jeta; Viradia, Arpana; Deshmukh, Bhargav; Chauhan, Sagar; Rothod, Santosh Dev (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Facial angiofibroma represents the most conspicuous and cosmetic disfiguring cutaneous manifestation of tuberous sclerosis, frequently leading to stigma for both the affected individuals and their families. Many times these angiofibromas are left untreated due to the dearth of minimally invasive therapeutic modalities. To combat this issue, topical administration of the mammalian target of rapamycin (mTOR) inhibitor, rapamycin, is recommended. Objective: The study aimed to evaluate the safety, tolerability, and efficacy of a topical combination of rapamycin and tacrolimus for the treatment of facial angiofibromas associated with tuberous sclerosis complex (TSC). Materials and Methods: This was a pilot study of 5 patients. A topical formulation was prepared by mixing 0.1% rapamycin with 0.1% tacrolimus 10 g ointment. Patients were instructed to apply the medication topically twice daily over the angiofibroma for 12 weeks, with regular follow-up visits every 3 weeks. We investigated the efficacy and safety using the “Facial angiofibroma severity index” (FASI). Results: The mean “facial angiofibroma severity index (FASI)” score was 8 ± 1.0, 6.4 ± 1.14, and 5.2 ± 0.84 at 0, 6, and 12 weeks, respectively, which was statistically significant. Transient irritation occurred in one patient. Conclusion: The topical combination of rapamycin and tacrolimus shows potential as an effective and well-tolerated option for facial angiofibroma. Limitations of the study include a small sample size and a relatively short follow-up duration.